2021
DOI: 10.1017/s0022050721000140
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Capacity and Dualism in Colonial States: The French Empire 1830–1962

Abstract: What was the capacity of European colonial states? How fiscally extractive were they? What was their capacity to provide public goods and services? And did this change in the “developmentalist” era of colonialism? To answer these questions, we use archival sources to build a new dataset on colonial states of the second French colonial empire (1830–1962). French colonial states extracted a substantial amount of revenue, but they were under-administered because public expenditure entailed high wage costs. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In their survey of colonial fiscal capacity, Frankema and Booth (2019) also highlighted the importance of local intermediaries in collecting taxes. Cogneau et al (2021) analysed multiple French colonies and found that colonies were able to extract large amounts with large variation in the mix of tax revenue. Overall, there is a large consensus that revenue was raised at a local level but little research on fees rather than taxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their survey of colonial fiscal capacity, Frankema and Booth (2019) also highlighted the importance of local intermediaries in collecting taxes. Cogneau et al (2021) analysed multiple French colonies and found that colonies were able to extract large amounts with large variation in the mix of tax revenue. Overall, there is a large consensus that revenue was raised at a local level but little research on fees rather than taxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this article, we build on that perspective, albeit in a context where sovereignty is embedded in the administration, considering the civil servants as central to the autonomy of the empire. That administration, in turn, constituted the core of the empire, a large share of the colonial economy depending on public investments and its consumption (Cogneau et al 2021). The colonial administration was very powerful in the colonies because part of the intellectual production came from its ranks (Sibeud 2002), and it faced no real counter-power in the absence of a true political representation in the colonies (Merle 2004).…”
Section: Professionalization Processes In Colonial Administrationsmentioning
confidence: 99%
“…Except in a few circumstances (Weldemichael, 2013), White Europeans almost exclusively colonized other countries. Relative to the imperial metropole, colonized places were sources of human and resource exploitation without strong and robust state administration (Cogneau et al, 2018a(Cogneau et al, , 2018bHerbst, 2014;Mamdani, 1999;Van Waijenburg, 2018). Imperial society was characterized by hierarchies between social groups along salient, qualitative characteristics-most typically race but also ethnicity and/or religion (Mamdani, 1999).…”
Section: Scope Conditionsmentioning
confidence: 99%